Development of a cell system for siRNA screening of pathogen responses in human and mouse macrophages - Li, Ning (Sci Rep, 2015)
Macrophages play a critical role in the innate immune response to pathogen infection, but few tools exist for systematic dissection of these responses using modern genome-wide perturbation methods. To develop an assay platform for high-throughput analysis of macrophage activation by pathogenic stimuli, we generated reporter systems in human and mouse macrophages with dynamic readouts for NF-κB and/or TNF-α responses. These reporter cells show responsiveness to a broad range of TLR ligands and to gram-negative bacterial infection. There are significant challenges to the use of RNAi in innate immune cells, including efficient small RNA delivery and non-specific immune responses to dsRNA. To permit the interrogation of the macrophage pathogen response pathways with RNAi, we employed the stably expressed reporter genes to develop efficient siRNA delivery protocols for maximal target gene silencing with minimal activation of the innate macrophage response to nucleic acids. We demonstrate the utility of these macrophage cell systems for siRNA screening of pathogen responses by targeting components of the human and mouse TLR pathways, and observe species-specific perturbation of signaling and cytokine responses. Our approach to reporter cell development and siRNA delivery optimization provides an experimental paradigm with significant potential for developing genetic screening platforms in mammalian cells.